Urban Resilience and Transportation Infrastructure Level in the Yangtze River Delta - Wang, Jian; Deng, Yuzhou; Qalati, Sikandar Ali; Qureshi, Naveed Akhtar (Frontiers in Environmental Science, 2022)
The development of urban resilience is inseparable from the construction of urban infrastructure. As an important lifeline of the city, transportation infrastructure is an important part of improving urban resilience. Studying the coordinated development degree of urban resilience and transportation infrastructure level is related to the future development of the city. On the basis of measuring the urban resilience and transportation infrastructure level in the Yangtze River Delta, this study uses the coupling coordination model and spatial autocorrelation model to explore the spatiotemporal evolution trend of the coupling coordination between urban resilience and transportation infrastructure level. The results show that first, the average development levels of urban resilience and transportation infrastructure are at the middle and lower levels, showing a spatial pattern of “high in the southeast and low in the northwest.” Second, the degree of coupling coordination fluctuates and rises and is in the transition stage from mild imbalance to primary coordination. Finally, the degree of coupling coordination is spatially positively autocorrelated, and the degree of agglomeration shows a stable development trend, but the difference of coordinated agglomeration between cities is expanding. To enhance the security and sustainable competitiveness of the Yangtze River Delta, this study argues that it is urgent to establish the concept of resilient urban development and promote the integration of urban agglomeration transportation infrastructure to promote the coordinated development of urban safety systems and infrastructure. Suggestions were recommended to efficiently improve the urban resilience and transportation infrastructure level in the Yangtze River Delta.